Gardening all-in-one for dummies ebook - The National Gardening Association (Dummies., 2011)
"God almighty first planted a garden: and, indeed, it is the purest of human pleasures." -- Sir Francis Bacon National surveys show that gardening has become the most popular, least exclusive hobby nationwide. From the balconies of Manhattan to the patios of Malibu to the backyards of Chicago, anybody with a few square feet of earth is doing their best to make their little corner of the world more gracious and beautiful. And the best thing is, you really don't have to be born with a green thumb to give life to a glorious garden. Anybody can do it with a little coaching. Which is where Gardening All-in-One For Dummies comes in. Puzzled by pruning? Baffled by bulbs? Can't tell a hosta from a hyacinth? Don't worry! This all-in-one reference delivers the know-how you need to transform your little patch of the outdoors into a blooming paradise. Drawing upon the expertise of the National Gardening Association, it gets you up to speed on: Basic gardening skills--from understanding your microclimate to using gardening tools to managing pests and common plant diseases How to design, plan and build a garden landscape that reflects your unique sense of style Selecting, planting and maintaining stunning roses Building a raised bed for your perennials and making them bloom in any climate Choose, grow and maintain annuals From amaryllis to spider dahlias to wood tulips--coaxing beauty from homely bulbs Enjoying nature's bounty by growing you own vegetables and herbs A veritable encyclopedia of gardening, this Gardening All-in-One For Dummies is an indispensable resource for novices and experienced gardeners alike. It brings together between the covers of a single volume seven great books covering: Gardening Basics Garden Design Roses Perennials Annuals Bulbs Vegetables and Herbs Your one-step guide to a beautiful garden, Gardening All-in-One For Dummies shows you how to experience the "purest of human pleasures" in your own backyard.